ON DOMINATION NUMBER OF CARTESIAN PRODUCT OF EVEN CYCLES - Jumani, A. D. (The Nucleus, 2011)
Let Î³(G) denote the domination number of the graph G and let Î³(GH) denote the domination number of the Cartesian product of the graphs and . Here in this note; let denote the cycle with three vertices and similarly, let denote the cycle with n vertices. The domination number of the Cartesian product of two even cycles and is characterized here, wherem< , with such that G H C3 Cn Cm Cn n m â‰¥ 4 m n mn Î³(C C )= 4 if and only if 2 divides mn 4 , that is, iff mn 2 | 4